Environment and stratigraphy of the archaeological site Lipovo in the Biebrza valley (Poland) - Frączek, Martin; Kalicki, Tomasz; Wawrusiewicz, Adam; Sanko, Aleksander F. (Journal of the Belarusian State University. Geography and Geology, 2019)
Study area is located in NE part of Poland in middle Biebrza Basin. Geological, geomorphological and geoarchaeological studies were conducted at the Lipowo site. A beginning of peat accumulation in the valley floor was radiocarbon dated at 8490 ± 80 BP (MKL3275) 76587347 cal. BC. Results of studies at Lipowo indicates some periods of climatic changes and an increase of morphogenetic processes. Climate fluctuations correlate very well with phases distinguished in Centraleuropean river valleys. SubNeolithic population inhabited the dry elevation at the bottom of river valleys. The Lipowo site should be attributed to hunting settlements. Such sites have a certain spatial arrangement. The impact of the population on the environment was insignificant. The research of the subNeolithic site on a sandy form surrounded by wetlands captured the homogeneity of the artifacts of the Neman culture. Organogenic layers with wellpreserved remainsof plants and animals allowed to determine the economic and food specifics of the studied society. The wellpreserved organic remains have made to determine the environmental conditions of the settlements and to obtain definitions of the radiocarbon age.
Keywords: Biebrza Basin; Neman culture; hunter-gatherers community; Late Neolithic